Sport-specific and anthropometric predictors of synchronised swimming performance - Sajber, D.; Peric, M.; Spasic, M.; Zenic, N.; Sekulic, D. (International Journal of Performance Analysis in Sport, 2013)
Predictors of sport-performance in synchronised swimming (Synchro) are rarely investigated. In this study we studied the applicability of sport-specific and anthropometric predictors of Synchro performance for young athletes (all females, 15-17 years of age, 6-8 years of experience in Synchro). Initially, four sport-specific tests (determining characteristic anaerobic and aerobic endurance) are examined with regard to its reliability. The results show the appropriate reliability of the four sport-specific tests (according to ICC, and the Bland Altman plot), while significant learning effects are found for one of the applied tests. Anthropometric indices (body height, body weight, body fat and lean body mass) are not significantly correlated to Synchro performance in solo-figures (criterion). Multiple regression shows the significant prediction of the Synchro solo-figure performance by means of sport-specific tests (R = 0.72; Rsq = 52%). The cross-validation sub-sample elicited a high correlation between predicted and achieved performance score (r = 0.80) Further studies are necessary to determine the longitudinal changes of the tested parameters and their influence on competitive achievement in this sport for different age categories.